The Influence of Internal Control and Information Technology on Fraud Prevention (Empirical study of individuals working in accounting, finance, taxation, auditing, and other financial management fields in Jakarta and surrounding areas) - Feber Sormin; Widury Siburian; Iwan Armawan; Lamhot Hutabarat; Fahri Solahudin (MOVE: Journal of Community Service and Engagement, 2026)
The purpose of this research is to examine and analyze the influence of internal control (IC) and Information Technology (IT) on fraud prevention (FP) among individuals working in the fields of Accounting, Finance, Taxation, Auditing, and other financial management in Jakarta and its surrounding areas. Research Method – This type of research is quantitative, using multiple linear regression analysis with primary data and ordinal scale data measurement collected by distributing questionnaires to individual respondents working in the fields of Accounting, Finance, Taxation, Auditing, and other financial management in Jakarta and its surrounding areas at several business/company locations. The number of samples used was 62 individual respondents working in the fields of Accounting, Finance, Taxation, Auditing, and other financial management in Jakarta and its surrounding areas. Data processing was carried out using the SPSS application. Research results: Internal control and information technology variables are proven to influence fraud prevention.